Relationship of Body Composition with Height and Weight in Attendants of Cancer Patients - Nadeem, Muhammad Sohaib; Ali, Ujala; Riaz, Bushra; Noreen, Tallat; Wahid, Mansoor; Gohar, Lubna (Pakistan Armed Forces Medical Journal, 2023)
Objective: To discern the relationship of height and weight with body composition in healthy attendants of cancer patients.Study Design: Cross-sectional study.Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Oct to Dec 2022.Methodology: A total of 226 healthy adults aged 19-47 years having similar daily physical activity levels were included. The body composition of study participants was evaluated using a bioelectric impedance analysis (BIA) machine. The weight of all participants was recorded with the help of a weighing machine. The participants' height was measured using a Harpenden Stadiometer and recorded.Results: Our study showed that weight had a significant positive correlation with body fat mass (rs value=0.83), skeletal muscle mass (rs value=0.763), total body water (rs value=0.704), fat-free mass (rs value=0.75) and per cent body fat (rs value 0.716). On the other hand, height had a negative but non-significant association with fat mass (rs value= 0.025) and a negative significant association with per cent body fat (rs value=-0.16). Height had a positive and significant association with fat-free mass (rs value=0.553), total body water (rs value=0.501) and skeletal muscle mass (rs value=0.505).Conclusion: Weight, if used alone, is not a good indicator of obesity or emaciation, and height has a negative association with fat mass.